Comparative Histological Evaluation of the Nictitating Gland Between Cat (Felis Catus) and Rabbits (Oryctolagus Cuniculus) (Indian Journal of Animal Production and Management, 2025)
This study focuses on the third eyelid gland morphology and histological examination  in Cats (Felis catus) and Rabbits. From adult rabbits and cats, ten nictitating  membranes were removed and sections examined under a light microscope, and a  macroscope. The entire length of a pigmented long, thin, curved structure resembling  the eyeball was the dorsal and ventral wings of cartilage — that was only complete  in the illustration. Sinus of the ventral wing was less than dorsal wing. There were  lymphoid nodules at the bottom of the refractive outside, and the cartilage had two  surfaces: the corneal and palmebral. The nictitating gland had an oval shape and  seemed to be a [complex acinar gland. The cartilage had isogenous chondrocyte  clusters which were diagnosable under a microscope. Further, these results offer  relevant reference data in supporting future anatomy studies and treatment about  feline third eyelid diseases and aging signs in ocular diseases. Rabbit Nictitating gland  Gland is embedded into the conjunctiva and lateral eyelid . It is called semi-circular  and smooth in form. From this intricate structure, rich in essential lubrication and  protection of the eyes serious and mucous secretions are emitted by a complicated  gland. By histology the gland is made up of acinar cells that are cuboidal or column in  appearance responsible for fluid secretion, Ductal cells displaying stratified cuboidal  or columnar epithelium and help in the transport of secretion, and Myoepithelial  cells as the antagonist in expulsion of glandular contents triggered by contraction.  The connective stroma of this gland, which keeps it from being squishy and gives it  shape, consists of collagen, fibroblasts and elastic fibers. Each of these traits clearly  points to the gland possing a unique function with respect to tear secretion and eye  health in rabbits.
Keywords: Comparative investigation; Nictitating; cats &Rabbits